Taking It Out on the Body? A Phenomenological Study of Young Adults' Gendered Experiences of Depression and Antidepressant Use. Issue 4 (1st October 2016) - Bornäs, Hanna; Sandell, Kerstin
Abstract: In this article, we use in-depth interviews with young adults in Sweden to explore the gendered and embodied experiences of depression and antidepressant use. Building upon previous phenomenological research, we analyse being depressed and on antidepressants as altered embodied states, in which corporealization—experiencing the body as a material object—is central. Feminist interventions by Toril Moi and Iris Marion Young inform our analysis of embodiment as gendered. The bodily facets of depression include the weight of the anxious body in crying and not sleeping, as well as the weakened or distorted relationship between body, mind and world in brooding thoughts and hopelessness. These experiences of corporealization are not expressed in gendered terms but, when acted out in depression, they do appear to be gendered. The female body becomes "the first battleground"—as the socially endorsed object upon which to act destructively. In contrast, male behaviour is not expressed as self-destructive, but projects in the world are emphasized at the cost of (bodily) well-being. Although antidepressants lift the corporeal weight of anxiety and low mood, they install a new, and in some respects more profound, corporealization of the body. This is expressed as feeling and caring less and being like a thing or machine. It can be understood in terms of an increased distance from the world—not articulated in gendered terms. As a way of existing in the world, the medicated state bears strong similarities to the depressed state from which it was originally an effort to escape. Thus, taking medication can be seen as yet another way of acting on the body as object. Furthermore, it could be suggested from our findings that when the body is not felt—when there is a breakdown of the meaningful relationship between the body and the world—the experience is less gendered.